PERSEBARAN DAN HABITAT PERSINGGAHAN BURUNG MIGRAN DI KABUPATEN NATUNA PROVINSI KEPULAUAN RIAU - Tri Haryoko (BERITA BIOLOGI, 2014)
Indonesia has become an important part in the flyway of migratory birds due to the existing of high variety of habitat types that support for their life.Until now, the migratory birds records from Natuna Regency, which is the border area of Indonesia located in the South China Sea, are limited. This study was aimed to determine distribution and stopover habitat of migratory birds in the Natuna Regency area. The study was conducted in 2011 and 2013.Result from observations showed 14 species of migratory birds that belongs to five district birds families were identified in this area.They were Ardeidae (two species), Charadriidae (four species), Scolopacidae (six species),Laridae(one species) and Hirundinidae (one species).Southern Bunguran area has the highest record of migratory birds than other regions in Natuna. The migratory bird used four types of stopover habitat in Natuna Regency. i.e mangrovs, coastal, lakes / wetlands and other open areas.